Inhibition of early EHDV2-Ibaraki infection steps in bovine cells by endosome alkalinization or ikarugamycin, but not by blockage of individual endocytic pathways - Malka, Maya; Czaczkes, Inbar; Kashkash, Shlomi; Shachar, Shirel; Bacharach, Eran; Ehrlich, Marcelo (Frontiers in Cellular and Infection Microbiology, 2025)
The Epizootic hemorrhagic disease virus (EHDV), an orbivirus, is the etiological factor of a fatal hemorrhagic disease of wild ruminants. A subset of EHDV serotypes, including the Ibaraki strain of EHDV2 (EHDV2-Ibaraki), infect and cause disease in cattle, thus posing a potential threat to livestock. As a member of the Sedoreoviridae family, the EHDV particle is devoid of a membrane envelope and is predicted to employ endocytic pathways for infection. However, the degree of dependence of EHDV2-Ibaraki on specific internalization pathways while infecting bovine cells (its natural host) is unknown. The endosome alkalinizing agent ammonium chloride blocked EHDV2-Ibaraki infection of Madin-Darby Bovine Kidney (MDBK) cells with dependence on its time of addition, suggesting the criticality of endosomal pH for the completion of early stages of infection. Treatment of cells within the alkalinization-sensitive window (i.e., before endosomal processing) with inhibitors of actin polymerization, macropinocytosis (amiloride), or dynamin GTPase activity (dynasore or dynole), or with the cholesterol-depleting agent methyl-β-cyclodextrin, failed to reduce EHDV2-Ibaraki infection. In contrast, in this same treatment time frame, ikarugamycin potently inhibited infection. Moreover, ikarugamycin inhibited interferon induction in infected cells and induced the accumulation of enlarged Rab7- and lamtor4-decorated vacuoles, suggesting its ability to block viral processing and modify late-endosome compartments. Notably, ikarugamycin treatment at initial infection stages, augmented the infection of MDBK cells with the vesicular stomatitis virus while inhibiting infection with bluetongue virus serotype 8. Together, our results point to differential antiviral effects of ikarugamycin on viruses dependent on distinct sets of endosomes for entry/processing.